Leveraging Artificial Intelligence in Human Resource Practices: Elevating Efficiency through Transhumanism - Sharma, Palki; Sharma, Bhavna; Sharma, Suprina; Mishra, Prakash; Aggarwal, Nidhi; Namdev, Divya; Bali, Santosh (Journal of Neonatal Surgery, 2025)
The current study examines the changing role of human resource management due to the integration of emerging approaches like geonomics, transhumanism and artificial intelligence in one way or other. Transhumanism and AI integration has significantly changed human resource processes, refining efficiency, accuracy, and strategic decision-making (Wenzel, R., & Van Quaquebeke, N., 2018). The major areas were impacted through AI includes Recruitment, employee engagement, performance management, and learning & development. Current study examines the review of existing literature related to AI integration in human resource management and transhumanist approach, particularly its impact, journal trends and related themes. A bibliography and content analysis of 75 articles selected through Scopus’ structured database is framed for a detailed analysis. It is revealed that AI has the capacity to transform conventional human resource management processes in favour of more flexible and data-driven strategies. The study also provides the advantages, difficulties, and potential applications of AI in HRM, giving readers a comprehensive understanding of how AI and transhumanism is shifting the human resource environment. away. Various maternal outcomes included postpartum hemorrhage, peripartum hysterectomy and blood transfusion. Perinatal outcomes included preterm birth, still birth, NICU admission and death.